Implementation of STEM-based Student Worksheet to Increase Student Entrepreneurial Innovation through the Development of Candied Nutmeg Products - Dara Sasmita; Muhammad Adlim; Abdul Gani; Muhammad Syukri (Postgraduate, University of Mataram, 2021)
The research has been carried out to develop STEM based Student Worksheets to determine their effectiveness in increasing students' entrepreneurial innovation through the development of candied nutmeg products and the responses of teachers and students to Student Worksheet. The research was conducted using the research and development (R & D) method using the ADDIE model. The sample in this study were 34 students of class XI IPA 1, selected using random sampling technique. The research data were obtained from expert assessment sheets, Student Worksheet and questionnaires for teachers and students. The results of the STEM-based Student Worksheet feasibility test by the experts showed that the Student Worksheet eveloped was classified as very worthy, with an average percentage value of 94.17%. The percentage of Yes responses obtained from teachers and students was 100.00% and 92.06% in the very good category. Based on the results of the study, it can be concluded that the developed STEM based Student Worksheet can increase students' entrepreneurial innovation and can be used as an alternative teaching material in craft and entrepreneurship materials, and get positive responses from teachers and students.